An evaluation of automated measurement of slice sensitivity profile of computed tomography image: field of view variations - Elvira Rizqi Widyanti; Choirul Anam; Eko Hidayanto; Ariij Naufal; Mohammad Haekal (Institute of Advanced Engineering and Science, 2023)
This study aims to evaluate the automated measurement of slice sensitivity profile (SSP) on the American Association of Physicists in Medicine (AAPM) computed tomography (CT) performance phantom for variations of slice thickness and field of view (FOV). The AAPM CT performance phantom was scanned using a Philips MRC 880 CT Scanner for variations of slice thickness and FOV. The slice thickness values were 1, 3, and 5 mm. The FOV values were 240, 300, 340, 400, and 440 mm. The automated SSPs and their fullwidth at half maximums (FWHMs) were automatically measured from the middle stair object of the phantom. To validate the automated measurement results, the FWHM values of SSPs obtained were compared to those from manual measurements. The differences between FWHMs from automated measurements and set slice thicknesses are less than 0.3 mm, while the differences between FWHMs from automated and manual measurements are less than 0.2 mm. The results from automated measurements are closer to the set slice thickness than those from manual measurements. This automated SSP measurement provides high accuracy and precision for both the slice thickness and the FOV variations.